The Mechanism of Pregnant Women's Marriage Out of Wedlock at the Sindangkasih District Religious Affairs Office from the Perspective of Islamic Law and Indonesian Positive Law - Septian, Muhamad; Atqia, Muhamad Reza; Laela, Novia; Yakub, Sandra Leoni Prakasa; Suryani, Santi (Jurnal El-Thawalib, 2025)
One phenomenon that continues to generate debate is the practice of marrying pregnant women out of wedlock. Therefore, the purpose of this study is to examine the practice of marrying pregnant women out of wedlock through a comparative analysis of Islamic law, Indonesian positive law, and their implementation at the KUA (Religious Affairs Office) in Sindangkasih District. The study used field research with a qualitative approach. Data sources included interviews with marriage registrars, observations of administrative procedures, and searches for marriage documents, while secondary data sources included fiqh literature, laws and regulations, and other documents. Data collection techniques included interviews with marriage registrars, observations of administrative procedures, and searches for marriage documents, and were analyzed using qualitative descriptive techniques. The results of the study indicate differing views in fiqh, with some schools of thought permitting marriage with men who impregnate before birth, while others require a delay to maintain clarity of lineage. In positive law, Article 53 of the Compilation of Islamic Law (KHI) takes a pragmatic approach, permitting such marriages as a form of protection for children and to prevent social stigma. Field findings show variations in practice among marriage registrars due to differences in moral interpretation, social pressure, and understanding of the rules. This study concludes that harmonization among fiqh norms, state regulations, and social dynamics is key to ensuring the continued relevance and contextual applicability of Islamic family law in modern society.